Density-Dependent Plant–Plant Interactions Triggered by Grazing - Kelemen, András; Tölgyesi, Csaba; Valkó, Orsolya; Deák, Balázs; Miglécz, Tamás; Fekete, Réka; Török, Péter; Balogh, Nóra; Tóthmérész, Béla (Frontiers in Plant Science, 2019)
Plant species performance in rangelands highly depends on the effect of grazing and also on the occurrence of unpalatable benefactor species that can act as biotic refuges protecting neighboring plants from herbivores. The balance between facilitation and competition may changes with the benefactor density. Despite the high number of studies on the role of biotic refuges, the density dependent effects of unpalatable herbaceous plants on the performance of other species, and on the habitat heterogeneity of rangelands are still unclear. Therefore, we performed a study to test the following hypotheses: (i) Performances of understory species follow a humped-back relationship along the density gradient of the unpalatable benefactor species. (ii) Small-scale heterogeneity of the vegetation decreases with increasing benefactor density. We studied meadow steppes with medium intensity cattle grazing in Hungary. We surveyed understory species’ performance (number of flowering shoots and cover scores) along the density gradient of a common, native unpalatable species (Althaea officinalis). Our findings supported both hypotheses. We found unimodal relationship between the benefactor cover and both the flowering success and richness of understory species. Moreover, small-scale heterogeneity declined with increasing benefactor cover. In this study we detected a humped-back pattern of facilitation along the density gradient of an herbaceous benefactor in pastures. Indeed, this pattern was predictable based on such conceptual models like “consumer pressure-abiotic stress model,” “humped-back model,” “intermediate disturbance hypothesis,” and “disturbance heterogeneity model”; but until now the validity of these relationships has not been demonstrated for herbaceous species. By the demonstration of this effect between herbaceous species we can better forecast the responses of grasslands to changes in management.